KERAGAMAN GENETIK BEBERAPA AKSESI JAGUNG DARI NUSA TENGGARA TIMUR BERDASARKAN PROFIL INTER SHORT SEQUENCE REPEAT (ISSR) - Yulita, Kusumadewi Sri; Naiola, BP (JURNAL BIOLOGI INDONESIA, 2013)
Maize (Zea mays L.) has become second most important cereal crops after rice in Indonesia. Maize is a staple foodand the main crop in subsistence dry land farming system in Nusa Tenggara Timur (NTT). Previous survey suggestedthat NTT may have contained considereable amount of local landraces of maize that have not been wellrecorded. Traditional farmers prefer to use traditional landraces than popular hybrid maize due to their superiorfeatures such as less susceptible to weevil attack and well adapted to local environment. Hence, farmers were continuouslygrow local landraces to meet the demand for their food security. Information on diversity of local landracesis very important for improving landrace germ plasm. The objective of this study is to assess genetic andphenotypic diversity of 15 accessions of maize from nine putative landraces collected from six locations in NTTbased on Inter Short Sequence Repeat (ISSR) fingerprints and few morphological charcters. Five ISSRâ??s primers(UBC 809, 822, 834, 876 and 892) were initially screened and two (UBC 809 and 834) were selected for the analysis.These primers generated 16 scorable bands with two monomorphic bands, i.e. UBC 809 at 700 bp and UBC834 at 900 bp. Clustering analysis was performed based on ISSR profiles using the UPGMA method. The range ofgenetic similarity value among accessions was 0.30-0.80 suggesting sufficient variation of gene pool existed amongaccessions. Combined data set of ISSR and morphological data suggested a higher diversity with a cofficient ofdistance range from 0.52 to 1.25. Same as a single data set deduced from ISSR profile, none of the accessionswere clustered according to their landraces nor their progeny.Keywords: Maize, NTT, ISSR, genetic diversity